Plato and Aristophanes : comedy, politics, and the pursuit of a just life - Marren, Marina (Rereading ancient philosophy., 2022)
"Plato and Aristophanes claims that our search for communal justice must start with self-examination. Marina Marren strikes up a conversation between three of Aristophanes's comedies-Assembly Women, Knights, and Birds-and Plato's Republic, prompting questions about one's convictions and actions"--